Optimization of Nanoliposome Formulations for Targeted Delivery of Hydrophobic Drugs - Verma, Anupam; Joshi, Diksha; Dixit, Varun; Kharche, Ajay; Uttamrao Borade, Amol; Panjwani, Deepak; Yadav, Rajiv; Gupta, Prashant; Singh, Ankita (Journal of Neonatal Surgery, 2025)
Nanoliposomes have emerged as promising nanocarriers for the targeted delivery of hydrophobic drugs, offering enhanced bioavailability, controlled release, and reduced toxicity compared to conventional drug delivery systems. This research focuses on optimizing nanoliposome formulations to improve the encapsulation efficiency, stability, and targeted delivery of hydrophobic therapeutic agents. Various fabrication techniques, including thin-film hydration, ethanol injection, and supercritical fluid methods, are assessed for their effectiveness in producing uniform, stable nanoliposomes with high drug loading capacity. Critical factors influencing formulation performance, such as lipid composition, particle size, surface modification, and encapsulation parameters, are systematically evaluated using a quality-by-design approach. Surface functionalization and stimulus-responsive mechanisms are explored to enhance targeting specificity and drug release kinetics at pathological sites. Challenges such as aggregation, drug leakage, and clearance by the reticuloendothelial system are addressed through advanced formulation strategies. The optimized nanoliposome formulations demonstrate superior skin permeability, sustained release profiles, and potential for clinical translation in cancer, fungal infections, and other therapeutic areas requiring hydrophobic drug delivery. This study underscores the pivotal role of nanoliposome engineering in advancing precision nanomedicine and improving therapeutic outcomes through tailored drug delivery systems (Anil Kumar, Jagdish Kumar Arun, Yogesh Matta, Balbeer Singh, Saurabh Sharma, 2024).